(untitled) (Teacher’s World: Journal of Education and Research, 2023)
This qualitative study aims at identifying the existing residential facilities and exploring the living experiences of the students with disabilities of Dhaka University. The students with disabilities and the house tutors of residential halls of Dhaka University were the respondents for the study. Findings from in-depth interview are extracted through thematic analysis which indicate various issues, limitations and areas of improvement. The findings are presenseted through several themes such as accessibility and mobility in the hall, facilities within the room, canteen and washroom, acceptance in the room and hall library, attitudes of the staff and authority. The study also investigates how these experiences affect the personal and academic lives of the students with disabilities. Based on the findings of the study the university authority can modify its ongoing reformation plan to create a more learning-friendly equitable and inclusive environment for the students with disabilities in the campus. Vol. 48 (University of Dhaka Centennial Special Issue), June 2022 p.95-107